Precipitation trends (1958–2021) on Ammassalik island, south-east Greenland - van der Schot, Jorrit; Abermann, Jakob; Silva, Tiago; Jensen, Caroline Drost; Noël, Brice; Schöner, Wolfgang (Frontiers in Earth Science, 2023)
Along with Arctic warming, climate models project a strong increase in Arctic precipitation in the 21st century as well as an increase in the ratio of liquid to total precipitation. In the precipitation-rich region of south-east Greenland, precipitation changes could locally have significant impacts on runoff. However, climate data are sparse in this remote region. This study focuses on improving our understanding of the past precipitation changes on Ammassalik island in south-east Greenland between 1958 and 2021. To assess past changes in air temperature at 2-meter and precipitation, output from a regional polar climate model (RACMO2.3p2) is evaluated with measurements from automatic weather stations in Tasiilaq and on Mittivakkat glacier. In addition, RACMO2.3p2 is used to assess past seasonal changes in air temperature at 2-meter, precipitation amount, precipitation phase and the altitude of the rain/snow boundary. We find that the climate model accurately represents the monthly average observed air temperature at 2-meter. While total precipitation is overestimated, interannual variability of precipitation is properly captured. We report a significant increase of summer temperature at 2-meter of +0.3 °C/decade (p<0.01) at Mittivakkat glacier and +0.2 °C/decade (p<0.01) in Tasiilaq in 1958-2021. For the subperiod 1990-2019, the trend in annual averages of temperature at 2-meter in Tasiilaq (+0.8 °C/decade, p=0.02) corresponds well to known temperature trends on the Greenland Ice Sheet within the same period. On Mittivakkat glacier a significant trend is not detected within this subperiod (+0.2 °C/decade, p=0.25). The modelled liquid precipitation ratio on Ammassalik island increased in all summer months (1958-2015) by +2.0/+1.9/+1.8 %/decade in June/July/August respectively. In July and August, these trends were stronger at higher elevations. No statistical evidence is found for trends in other seasons. We also identify monthly increases in the altitude of the rain-to-snow boundary (+25/+23/+20 m/decade in July/August/September respectively).